Anti-Saccharomyces cerevisiae and antineutrophil cytoplasmic antibodies as predictors of inflammatory bowel disease. Issue 9 (11th August 2005) - Israeli, E; Grotto, I; Gilburd, B; Balicer, R D; Goldin, E; Wiik, A; Shoenfeld, Y
Abstract : Background and aims: Several antibodies have been reported in the sera of patients with Crohn's disease (CD) and ulcerative colitis (UC). The most commonly described are anti- Saccharomyces cerevisiae mannan antibodies (ASCA) in CD and perinuclear antineutrophil cytoplasm antibodies (pANCA) in UC. Familial clustering of these antibodies has been described, suggesting they might be genetic markers. Our aim was to investigate the presence of these antibodies before the emergence of overt clinical manifestations. Methods: Since 1980, the Israeli Defense Force (IDF) Medical Corps Serum Repository has stored serum samples obtained systematically from 5% of all recruits on enlistment, and from the same population on discharge from compulsory military service. We evaluated serum samples obtained from 32 subjects with CD and eight with UC before they were clinically diagnosed, along with samples from matched controls. Results: ASCA were present in 10/32 (31.3%) CD patients before clinical diagnosis compared with 0/95 (0%) controls (p<0.001). None of the eight patients with serum samples available before diagnosis of UC were ASCA positive. ASCA was positive in 54.5% of patients after diagnosis of CD. The mean interval between ASCA detection and diagnosis was 38 months. In 90% of patients, antibodies were detected in the first available serum sample; therefore, measurements of the average time from the presence of ASCA to diagnosis may be even longer. pANCA were present in 2/8 (25%) patients with available sera before the diagnosis of UC. None of their 24 matched controls were positive (p = 0.014). Conclusions: ASCA and pANCA may predict development of inflammatory bowel disease years before the disease is clinically diagnosed.